2022
DOI: 10.1177/10600280221094571
|View full text |Cite
|
Sign up to set email alerts
|

The Use of High-Dose Corticosteroids Versus Low-Dose Corticosteroids With and Without Tocilizumab in COVID-19 Acute Respiratory Distress Syndrome

Abstract: Background: Corticosteroids and tocilizumab have been shown to improve survival in patients who require supplemental oxygen from coronavirus disease 2019 (COVID-19) pneumonia. The optimal dose of immunosuppression for the treatment of COVID-19 acute respiratory distress syndrome (ARDS) is still unknown. Objective: The objective of this study was to evaluate the effectiveness and safety of high- versus low-dose corticosteroids with or without tocilizumab for the treatment of COVID-19 ARDS. Methods: This was a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Other studies [7,8,10,11,19], including platform trials [5,6], have reported a favorable effect of tocilizumab in alpha, beta or gamma cases; however, the benefit of tocilizumab in patients infected with delta, which is reported to be more virulent [20], or in patients infected with omicron, which is, in contrast, reputed to be less virulent [21], remained disputable. To the best of our knowledge, this study was the first to report the use of tocilizumab in a large cohort of severe COVID-19 patients infected with the delta and omicron VOC, suggesting that, among the patients developing a severe form of the disease, the mortality rates were similar in the omicron and delta cases, as it has been reported with previous VOCs [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies [7,8,10,11,19], including platform trials [5,6], have reported a favorable effect of tocilizumab in alpha, beta or gamma cases; however, the benefit of tocilizumab in patients infected with delta, which is reported to be more virulent [20], or in patients infected with omicron, which is, in contrast, reputed to be less virulent [21], remained disputable. To the best of our knowledge, this study was the first to report the use of tocilizumab in a large cohort of severe COVID-19 patients infected with the delta and omicron VOC, suggesting that, among the patients developing a severe form of the disease, the mortality rates were similar in the omicron and delta cases, as it has been reported with previous VOCs [14].…”
Section: Discussionmentioning
confidence: 99%
“…This deregulation in cytokine secretion was mainly characterized by an extensive expression of interleukin-6 (IL-6) and tumor necrosis factor α (TNF-α) which injure the lungs and other organs to a lesser extent [1,2]. Unsurprisingly, corticosteroids were the first immunomodulatory medications to demonstrate a mortality benefit among patients with coronavirus disease 2019 (COVID- 19) and are now a cornerstone of COVID-19 treatment in patients receiving respiratory support [3].…”
Section: Introductionmentioning
confidence: 99%
“…One may wonder whether the dose of tocilizumab is influenced by the different doses of corticosteroids. Multiple studies have investigated the benefit of using a higher corticosteroid dose compared to the standard 6 mg and found that doses >6 mg do not have a better mortality benefit [ 18 , 19 ]. While we observed that our low dose tocilizumab group used a higher median dose of corticosteroids, our overall cohort also did not find additional mortality benefit.…”
Section: Discussionmentioning
confidence: 99%
“…As commented, the study by Ullah et al [67], highlights the role of tocilizumab in improving performance on an institutional treatment including dexamethasone over coagulopathy control, supporting our model results. Furthermore, the evidence regarding the use of biologics targeting IL-6R -including tocilizumab-and IL-6 downstream JAK proteins since we started this study has increased [40,41,[86][87][88][89][90], to the point that its use is recommended in the NIH guidelines for treatment of hospitalized patients requiring oxygen or assisted ventilation or oxygenation, in combination to dexamethasone [91] The methodology employed for the modelling, considering the whole human protein network and a wide range of drug-pathology relationships for the training (S4 Table ), allow the TPMS-based models to infer biological and functional information on not-so-well documented therapeutic areas by connecting a wider biological knowledge spectrum, as shown in previous studies [47,55,83,84].Therefore, while the models and conclusions could be updated over time as new information is generated, potentially improving accuracy of the results and allowing exploring unanswered questions in COVID-19 evoked ARDS, our approach has provided results that are in agreement with current molecular pathophysiological and clinical knowledge, providing protein candidates as response biomarkers and supporting the role of the approach in exploring mechanistic insights on the effects of current available therapies.…”
Section: Plos Onementioning
confidence: 99%